Hazardous materials chemistry - Bevelacqua, Armado S. (Thomson/Delmar Learning, 2006)
The second edition of Hazardous Materials Chemistry explores basic principles of chemistry and toxicology so that first responders can efficiently identify a chemical hazard, anticipate potential outcomes, and make safe and informed decisions. Step-by-step coverage of the names of chemical families and their general categorical hazards and incompatibilities enable readers to not only grasp the science behind the chemicals and reactions but also apply principles to actual incidents. An all-new chapter on infrared spectroscopy brings the book up to date with the latest detection technology used in fire departments today.